Constraints on the Role of Laplace Pressure in Multiphase Reactions and Viscosity of Organic Aerosols - Sarah S. Petters (Geophysical Research Letters)
Abstract Aerosol chemistry has broad relevance for climate and global public health. The role of interfacial phenomena in condensed‐phase aerosol reactions remains poorly understood. In this work, liquid drop formalisms are coupled with high‐pressure transition state theory to formulate an expression for predicting the size‐dependence of aerosol reaction rates and viscosity. Insights from high‐pressure synthesis studies suggest that accretion and cyclization reactions are accelerated in 3–10‐nm particles smaller than 10 nm. Reactions of peroxide, epoxide, furanoid, aldol, and carbonyl functional groups are accelerated by up to tenfold. Effective rate enhancements are ranked as: cycloadditions >> aldol reactions > epoxide reactions > Baeyer‐Villiger oxidation >> imidazole formation (which is inhibited). Some reactions are enabled by the elevated pressure in particles. Viscosity increases for organic liquids but decreases for viscous or solid particles. Results suggest that internal pressure is an important consideration in studies of the physics and chemical evolution of nanoparticles.